Perbaikan Proses Transaksi Kepersonaliaan Departemen C&B Services PT. X - Livia Vionita; Herry Christian Palit (Jurnal Titra, 2016)
PT. X is a multinational manufacture company which produces consumer goods. PT. X expects to improve personnel transaction processes in C&B (Compensation and Benefits) Services Department by reducing steps in each transaction by at least 5% and the average processing time by at least 10%. The steps to achieve the objectives are evaluating the existing steps then simplifying it. Workload calculation using FTE (Full Time Equivalent) method by simplifying the task measurement and converting work load hours into number of human resources required. The implementation results show the steps are decreased by 18.06% and average processing time is decreased by 20.79%, which is exceeding company’s targets. These results affect the Specialist’s work load as well as total number of human resources from 6 to 5 personnels.